Functional Integrity of the Inferior Vestibular Nerve and Posterior Canal BPPV - Shupak, Avi; Falah, Rohi; Kaminer, Margalith (Frontiers in Neurology, 2020)
The functional integrity of the inferior vestibular nerve (IVN) may be evaluated by the cervical vestibular evoked myogenic potential (cVEMP), which requires signal transmission via the nerve. As functional integrity of the IVN innervating the posterior semicircular canal (PSCC) is required to produce the typical positioning vertigo and nystagmus characterizing PSCC benign paroxysmal positional vertigo (PCBPPV), we hypothesized that normal cVEMPs would be found in most PCBPPV patients. 24 patients participated in a prospective cohort study. All were treated by canal repositioning maneuver, had air-conduction cVEMP and Videonystagmography (VNG). Follow up evaluations including history, and otoneurological bed-side examination were carried out 1, 3, 6 and 12 months after the initial treatment. At the last follow-up the patients filled the Dizziness Handicap Inventory (DHI) questionnaire. Normal cVEMPs were recorded in 19 (79%) and were absent in 5 (21%) of the subjects. The average DHI in the patients with normal cVEMP was 16.42+17.99 vs. 0.4+0.89 among those with pathological cVEMP (p<0.04, Mann Whitney test). 13 (54%) patients experienced recurrent PCBPPV (rPCBPPV). The average DHI score was significantly higher among patients having recurrence (22.15+18.61) when compared to those with complete cure (2.36+5.98; p<0.003, Mann Whitney test). 10 (77%) of the subjects with rPCBPPV had normal and 3 (23%) had pathological cVEMP as compared to 9 (82%) and 2 (18%) subjects in the non-recurrent (nrPCBPPV) group (Fisher's exact test – not significant). cVEMP p13 and n23 wave latencies and amplitudes, inter-aural differences in p13-n23 peak to peak amplitudes, and response thresholds did not differ between the groups. No differences were found between the rPCBBPV and nrPCBBPV groups in VNG caloric lateralization and directional preponderance values. We have found that in most cases, PCBPPV symptoms and signs are associated with normal cVEMP response supporting the role of IVN functional integrity. The absent cVEMPs in the minority of patients, although having similar clinical presentation, raise the possibility that the ipsilateral saccule is affected by the same pathology causing degeneration of the utricle macula. Alternatively, lacking inhibitory stimuli from the involved ipsilateral utricle or partial degeneration of the IVN and ganglion could explain the diminished cVEMP response.